1984
DOI: 10.1111/j.1399-3054.1984.tb02797.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene production and toxigenicity of methionine and its derivatives with riboflavin in cultures of Verticillium, Fusarium and Colletotrichum species exposed to light

Abstract: 1984. Ethylene production and toxigenicity of methionine and its derivatives with riboflavin in cultures of VerticUUum, Fusarium and Colletotrichum species exposed to light. Ethylene was produced by VerticUUum dahliae Kleb. grown in liquid Czapek's medium. The rate of ethylene production was enhanced by light but was not affected by shaking or the growth rate of the cuitures. L-, D-and OL-methionine, DL-ethionine and a-keto-y-methylthiobutyric acid (KMBA) were good substrates for ethyiene production. KMBA may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…However, previous studies showed that the amount of in vitro ethylene production is not always directly related to virulence of V. dahliae (DeVay, 1989;Wiese and DeVay, 1970;Tzeng and DeVay, 1985;Chagué et al, 2006). For example, a highly virulent V. dahliae cotton defoliating strain produced less ethylene than a less virulent non-defoliating strain in culture (Tzeng and DeVay, 1984). As plants also produce considerable higher amounts of ethylene, it is unclear whether ethylene synthesized during infection was derived from the host, the pathogen, or both.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous studies showed that the amount of in vitro ethylene production is not always directly related to virulence of V. dahliae (DeVay, 1989;Wiese and DeVay, 1970;Tzeng and DeVay, 1985;Chagué et al, 2006). For example, a highly virulent V. dahliae cotton defoliating strain produced less ethylene than a less virulent non-defoliating strain in culture (Tzeng and DeVay, 1984). As plants also produce considerable higher amounts of ethylene, it is unclear whether ethylene synthesized during infection was derived from the host, the pathogen, or both.…”
Section: Discussionmentioning
confidence: 96%
“…These transcriptional changes led to reduced fungal growth in vascular tissues and symptom development in etr1‐1 plants. It is an open question whether V. dahliae employs ET perception via ETR1 to escape the activation of the plant defence mechanisms, as it is known that V. dahliae produces ET in vitro (Tzeng and DeVay, 1984). Verticillium dahliae constitutes a serious threat for a number of crops, as there is no chemical treatment; in the present study, we have attempted to elucidate and show the key role of the ETR1 gene in a plant defence mechanism against this vascular wilt pathogen as a step towards the understanding and uncoupling of a plant–pathogen interaction that threats and reduces the agricultural capita in a world that demands additional safer plant products.…”
Section: Discussionmentioning
confidence: 99%
“…In higher organisms, the KMBA pathway has been described in the yeast Saccharomyces cerevisiae and in the filamentous fungus P. digitatum [14]. In addition, it has been suggested as a pathway of ethylene biosynthesis in the fungi F. oxysporum , Colletotrichum dematium , in several species of Verticillium [15] and in Laccaria laccata [16].…”
Section: Introductionmentioning
confidence: 99%